2012
DOI: 10.1258/jtt.2012.111009
|View full text |Cite
|
Sign up to set email alerts
|

A systematic Review of the Mediating Role of Knowledge, Self-efficacy and Self-care Behaviour in Telehealth Patients with Heart Failure

Abstract: Citation: Ciere, Y., Cartwright, M. & Newman, S. P. (2012). A systematic review of the mediating role of knowledge, self-efficacy and self-care behaviour in telehealth patients with heart failure. Journal of Telemedicine and Telecare, 18(7), pp. 384-391. doi: 10.1258/jtt.2012.111009 This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent SummaryWe conducted a systematic review of controlled trials and pre-post studies to examine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 46 publications
1
51
0
Order By: Relevance
“…19,40,45 However, little is known about the processes by which telehealth may do this. 22 The present study provides insights into the mechanisms by which patients can be more engaged with their health care and self-management, which can lead to a better understanding of their condition, improved health behaviours and improved self-management, as perceived by the patient.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…19,40,45 However, little is known about the processes by which telehealth may do this. 22 The present study provides insights into the mechanisms by which patients can be more engaged with their health care and self-management, which can lead to a better understanding of their condition, improved health behaviours and improved self-management, as perceived by the patient.…”
Section: Discussionmentioning
confidence: 89%
“…[18][19][20][21] However, a review investigating the role of knowledge, self-efficacy and self-care behaviour in Telehealth patients with heart failure concluded that there was insufficient evidence to support or disprove that clinical outcomes and quality of life are affected by these factors. 22 This paper reports the findings from the evaluation of an NBN Telehealth trial of Feros Care's My Health Clinic at Home (MHCAH) system. The aim of the evaluation was to explore the extent to which the NBN could enable health services to be delivered in the home and affect patients' chronic disease management.…”
mentioning
confidence: 99%
“…Nine of the 51 retrieved articles reported on studies related to congestive heart failure [8][9][10]14,17,25,35,36,38]. The typical clinical parameters being measured (usually in a daily basis) were blood pressure, weight, heart rate, and oxygen saturation.…”
Section: Congestive Heart Failurementioning
confidence: 99%
“…46 It has been shown that up to 64% of HF hospitalizations could be prevented by adherence to the prescribed medication and diet, but up to 90% of HF patients do not fully adhere to their recommended regimens. 47 Self-efficacy is defined as the confidence one has in performing a specific behavior and is essential to making sustained behavioral changes. Weaker self-efficacy beliefs are associated with nonadherence to self-care recommendations for HF.…”
Section: Clinical Perspectives: Benefits and Disadvantagesmentioning
confidence: 99%
“…Weaker self-efficacy beliefs are associated with nonadherence to self-care recommendations for HF. 47 The positive effect of such an intervention was seen in two studies: one study tested a sliding scale diuretic titration protocol in HF patients where patients using this self-management strategy had increases in their exercise tolerance, quality of life, and fewer emergency department visits; 48 and the other study admitted HF patients randomized to an HF management group and taught self-management skills compared with usual care. 49 Unfortunately, the majority of patients with HF are not followed in an HF disease management program but by primary care physicians.…”
Section: Clinical Perspectives: Benefits and Disadvantagesmentioning
confidence: 99%